Síndrome de Cushing ACTH-dependiente durante el embarazo tratado con metirapona - Catarina Machado; Sara Monteiro; Marta Barbosa; Maria João Oliveira (Galicia Clínica, 2021)
Introduction: Cushing’s syndrome (CS) rarely occurs during pregnancy due to the influence of the hypercortisolism on the reproductive axis, with only a few cases described. Limited literature on its management is available. Case report: We present a case of a 32 year-old woman diagnosed with ACTH-dependent CS and no clear pituitary lesion on the MRI. After initiating treatment with ketoconazole, she discovered she was 8-weeks pregnant and ketoconazole was stopped. A conservative management was initially decided and no complications were documented during the first trimester of pregnancy. At 26 weeks of gestation, the patient developed gestational diabetes and treatment with metyrapone was started. Metyrapone was well tolerated and the pregnancy proceeded without further complications. She gave birth to a male infant, via cesarean section, at 36 weeks of gestation. No apparent teratogenic effects of metyrapone were observed. Conclusion: Many authors consider surgery as the first-choice treatment in pregnant women with CS but there is no consensus on the best management of these very rare cases. In our case, pharmacological treatment with metyrapone was a safe alternative to surgery in controlling hypercortisolism.